Aspirations Unfulfilled : Malaysia's Cost of Living Challenges - World Bank (World Bank, Malaysia, 2020)
Despite Malaysia’s low and stable inflation rate, there has been an ongoing debate regarding perceived increases in the cost of living in the country. The concerns are frequently expressed in public policy discussions, the mass media, and private conversation. The issue has featured prominently in public and private discourse for years, dating back at least to the rationalization of the fuel subsidy in December 2014 and the introduction of the Goods and Services Tax in April 2015. More recently, there has been a robust public debate about whether Malaysia should raise the nationally defined poverty line. These concerns have emerged during a period of low inflation; the average annual headline inflation rate stood at less than 2 percent beginning in January 2015 and has declined to less than 1 percent since January 2018, well below the growth rates of the economy and average nominal incomes. In this context, the “cost of living” is frequently used as a catchall term that may reflect wider developments in the economy and the associated impacts on household budgets and well-being. While the discussion is usually framed as an issue of the rising costs of goods and services, the core issues for most Malaysians extend beyond prices. These include lagging income growth and greater indebtedness that results in less disposable income and inadequate financial savings. In addition, rising home prices also feed into the concerns of many Malaysians about housing affordability and the cost of living.